Dietary exposure to acrylamide of university students in Ningxia of Northwest China and the effect on their neurobehavioral performance and oxidative stress in serum. Issue 2 (17th October 2022) - Gao, Qinghan; Xue, Yanzhong; Yuan, Xiao; Gao, Hua; Wu, Chunsen
Abstract: This study aims to investigate dietary exposure to acrylamide (AA) and also make an assessment of its effect on the neurobehavioral performance and oxidative stress in the serum of university students in Ningxia. The place primarily consists of arid, dry desert, and wheat‐based foods are the staple food there. A total of 803 university students in Ningxia participated in this cross‐sectional study. Diet intake of AA was estimated with FFQ. The AA risk was calculated as margin of exposure (MOE) values. NCTB questionnaires were used to assess neurobehavioral performance. The serum oxidative stress levels of the university students were measured as GSH, MDA, and SOD. The mean for AA exposure of university students was 0.515 μg kg −1 bw day −1 . The highest contributor was traditional Chinese grain products, representing 34.71% of the total daily AA intake. Followed were deep‐fried potato products, traditional Western grain products, soft drinks, and nuts, which accounted for 23.87%, 16.59%, 11.15%, and 11%, respectively. The median AA exposure were 480 (BMDL10  = 0.18 mg kg −1 bw day −1 ) and 827 (BMDL10  = 0.31 mg kg −1 bw day −1 ), respectively. The results indicated that diet AA may have an effect on the emotional status and neurobehavior among this population. We observed no significant differences in oxidative stress under the three levels of AA exposure ( p  > .05). It suggests a health concern for university students in Northwest China that should get society's attention. Abstract : This study aims to investigate dietary exposure to acrylamide (AA) of university students in the Northwest China and the effect on their neurobehavioral performance and oxidative stress in serum. The results indicated that diet AA may affect the emotional status and neurobehavioral performance in this population. We observed no significant differences in oxidative stress under the three levels of AA exposure ( p  > .05). It suggests that there is a health concern with respect to university students in Northwest China.